Asistensi Laporan SPT Tahunan Orang Pribadi E-Filling Melalui Kegiatan Relawan Pajak Pada Tahun 2021 - Endro Andayani; Devi Anggraeni; Sya’adan Abdullah (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2022)
In March 2021 the Director General of Taxes in collaboration with the Tax Center Institute Stiami involved 12 students for tax volunteer activities by placing 12 students at the KPP Pratama Jakarta Gambir Empat. The purpose of this activity is to assist individual taxpayers in reporting their 2020 SPT using electronic reports, so that taxpayers who do not understand information technology can be assisted in filling out the SPT. The role of Tax Volunteers is expected to increase taxpayer compliance. Therefore, to be able to serve taxpayers well, they are equipped with knowledge in the form of communication, tax volunteer ethics, e SPT OP, and e filling. The implementation method follows the guidelines set by the Tax Service Office, namely there are those who wait at the KPP, and visit the Taxpayer's Location. The results of the activity show that for 1 month 12 tax volunteers helped fill out the SPT OP as many as 562 taxpayers.